The Role of Distress Tolerance in the Relationship Between Affect and NSSI - Slabbert, A.; Hasking, Penelope; Notebaert, L.; Boyes, Mark (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Objective: Non-suicidal self-injury (NSSI), the deliberate and self-inflicted damage of body tissue, typically serves an emotion regulation function. Both negative and positive affectivity have been associated with NSSI, as has low distress tolerance. In the current study, we tested whether relationships between both negative and positive affectivity and NSSI are moderated by the four facets of distress tolerance (tolerance, absorption, appraisal, regulation) captured by the Distress Tolerance Scale. Methods: A sample of 531 university students completed well-validated measures of NSSI, negative affectivity, positive affectivity, and distress tolerance. Results: Findings indicate that negative and positive affectivity, as well as the appraisal (i.e. negative perceptions of distress) and absorption (i.e. allocation of attention to distress) facets of distress tolerance, were directly associated with NSSI. Positive affectivity and appraisal also interacted in differentiating participants with recent, lifetime and no history of NSSI. Specifically, the association between negative perceptions of distress and self-injury was weaker at high levels of positive affectivity. Positive affectivity and absorption also interacted to differentiate between individuals with no history of NSSI and individuals who recently engaged in NSSI. Specifically, positive affectivity was negatively associated with self-injury, but only among individuals who allocate less attention to their distress. Conclusions: Considering the independent roles of negative and positive affectivity alongside specific facets of distress tolerance and their interactions with emotional experience, may enhance understanding of NSSI. Prevention and intervention initiatives that assist regulation of negative affectivity, increase positive affectivity, and improve distress tolerance, may reduce the likelihood of engaging in self-injury.Highlights Negative and positive affectivity are independently associated with NSSI Appraisal and absorption facets of distress tolerance are associated with NSSI Positive affectivity moderates associations between appraisal and absorption and NSSI.